Blue helmets and grey zones: Do UN multidimensionnal peace operations work? - Louise Riis Andersen; Peter Emil Engedal (Danish Institute for International Studies (DIIS), 2013)
Multidimensional peace operations have emerged as one of the key instruments for addressing and managing the complex challenges related to violent conflict and state fragility in the Global South. Based on a reading of existing literature, this study provides an overview of what we know about the UN's ability to assist wartorn societies in laying the foundations for lasting peace. The basic message is that peacekeeping works, but statebuilding fails. In general, multidimensional UN-led peace operations have been successful at preventing the resumption of war, yet they have not succeeded in establishing effective and legitimate institutions of governance. The report also concludes that, while the system is far from perfect, the UN peacekeeping apparatus has been reformed and strengthen considerably in recent decades. Outstanding challenges relate to contextualising interventions and ensuring local ownership, as well as to maintaining the normative consensus on the role of UN peace operations.
Keywords: 300